Crystal structure of bis[1,3,4,5-tetramethyl-1H-imidazole-2(3H)-thione-κS]chloridocopper(I) - Flörke, Ulrich (Acta Crystallogr Sect E Struct Rep Online, 2014)
The molecular structure of the title compound, [CuCl(C(7)H(12)N(2)S)(2)], shows a slightly distorted trigonal–planar coordination geometry of the Cu atom. The Cu—Cl bond measures 2.2287 (9) Å, and the two Cu—S bonds are significantly different from each other, with values of 2.2270 (10) and 2.2662 (10) Å. Also, the S—Cu—Cl angles differ, with values of 113.80 (4) and 124.42 (4)°, while the S—Cu—S angle is 121.51 (4)°. The two imidazole rings are almost parallel, making a dihedral angle of 2.1 (2)°. In the crystal, the shortest C—H⋯Cl interactions stabilize a three-dimensional network with molecules linked into centrosymmetric dimers that are stacked along the b-axis direction.